2022
DOI: 10.3390/s22072509
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Climate Change and Human Activities on Vegetation Development in Northeast China

Abstract: Vegetation in Northeast China (NEC) has faced dual challenges posed by climate change and human activities. However, the factors dominating vegetation development and their contribution remain unclear. In this study, we conducted a comprehensive evaluation of the response of vegetation in different land cover types, climate regions, and time scales to water availability from 1990 to 2018 based on the relationship between normalized difference vegetation index (NDVI) and the standardized precipitation evapotran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 58 publications
3
6
0
Order By: Relevance
“…Several studies confirmed that there was a significant upward trend in vegetation cover in the Northeast after 2000 (M. L. Li, Yan, et al, 2022; Shi et al, 2022). Our results verified that a series of ecological restoration projects in northeastern China have gone accomplished in improving soil erosion (Xue et al, 2022). However, the water erosion modulus of grassland ecosystems showed a decreasing trend (Table 4), which was related to the high sand content of grasslands and low vegetation cover.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies confirmed that there was a significant upward trend in vegetation cover in the Northeast after 2000 (M. L. Li, Yan, et al, 2022; Shi et al, 2022). Our results verified that a series of ecological restoration projects in northeastern China have gone accomplished in improving soil erosion (Xue et al, 2022). However, the water erosion modulus of grassland ecosystems showed a decreasing trend (Table 4), which was related to the high sand content of grasslands and low vegetation cover.…”
Section: Discussionsupporting
confidence: 89%
“…On the time scale, the vegetation NDVI in the study area of Momoge showed a fluctuating upward trend from 1984 to 2020, and the vegetation growth status was generally good; however, the vegetation NDVI continued to decline in the middle of the study, which is consistent with the conclusion obtained by other researchers (Xue et al, 2022). In addition, the trend of high vegetation cover in the study area increased before 2000 and decreased after 2005, whereas the trend of vegetation cover and middle and high vegetation cover changed in the opposite direction.…”
Section: Temporal and Spatial Characteristics Of Vegetation Coversupporting
confidence: 91%
“…Increasing vegetation cover not only increases soil organic carbon and total nitrogen, but also enhances ecosystem services, lessens soil erosion, and modifies regional climate [49,50]. This is supported by the improvement in climatic conditions from 2002 to 2013 [48] and the decreased trend of drought area at multiple time scales (Figures 3b and 4). However, most of the planted trees that are utilized for revegetation are still young, have underdeveloped root systems, and can only draw water from surface soil.…”
Section: Driving Factors Of Drought Dynamics and Mutation Pointsmentioning
confidence: 79%
“…On the other hand, studies have reported trends in greening and productivity growth in NEC [46,47]. The vegetation impacted by human activities had a degradation trend from 1990 to 2001 and an increase after 2001, with 93% of this improved trend being linked to human activity [48]. Increasing vegetation cover not only increases soil organic carbon and total nitrogen, but also enhances ecosystem services, lessens soil erosion, and modifies regional climate [49,50].…”
Section: Driving Factors Of Drought Dynamics and Mutation Pointsmentioning
confidence: 99%